Somatometric Characteristics of the Grey Wolf (Canis lupus) in Bulgaria - Ahmed, Atidzhe; Koichev, Blagoy; Andreev, Rossen; Stepanov, Ivan; Savev, Peter (Silva Balcanica, 2024)
Grey wolf ( Canis lupus Linnaeus 1758) is the largest representative of the Canidae family in Bulgaria. It inhabits almost the whole territory, most frequently the mountainous and hilly areas. The grey wolf is a hunting species in the country. Despite this, there is little information in the literature on its size. The aim of this work was to provide the first systematized data of the somatometric characteristics (weight – P; total body length – L; length of the body to the base of the tail – Lb; tail length – Lo and height at the withers – Hb) of the grey wolf in Bulgaria and to establish what is the degree of their sexual dimorphism. We found that the adult males are 24.3% heavier than the females (t=4.46; p<0.001). They also have a longer body by 8.8% (t = 3.66; p<0.001) and a greater height by 6.5% (U=546; p=0.005). The smallest difference (6.2%) between the two sexes was observed in tail length (U=629.5; p=0.03). The results of our study support the clear sexual dimorphism established in other wolf populations. Further studies are needed to link the wolf ’s body size data with prey type data in the respective areas for more clarity. This will be beneficial both for better wolf population management and for the accumulation of a database.